Nano-Tera.ch Engineering the Future of Systems for Health, Environment and Energy - Leblebici, Anil; Mayor, Patrick; Rajman, Martin; De Micheli, Giovanni (Springer International Publishing : Imprint: Springer, 2019)
This book presents the overall vision and research outcomes of Nano-Tera.ch, which is a landmark Swiss federal program to advance engineering system and device technologies with applications to Health and the Environment, including smart Energy generation and consumption. The authors discuss this unprecedented nation-wide program, with a lifetime of almost 10 years and a public funding of more than 120 MCHF, which helped to position Switzerland at the forefront of the research on multi-scale engineering of complex systems and networks, and strongly impacted the Swiss landscape in Engineering Sciences. .